A resistência do professor as mudanças de metodologia de ensino - Cavalcanti, Edmar de Carvalho (1980)
The analysis and interpretation of the data showed the teacher to be the support for the functioning of the meth odological changes in the teaching procedures, thus permiting the recognition of the viability and the execution of the main purpose of this work, which is to consider the need of the teacher to be previously aware of these changes in order to accept them. Futhermore, in the studies for the implementation of a new methodology of teaching, the psychological and social componentes intervening in the teacher's work, should be taken into consideration.